Grass carp SERPINA1 inhibits GCRV infection through degrading CF2 - Li, Yangyang; Chen, Liangming; Huang, Rong; Li, Yangyu; Yang, Cheng; Gui, Bin; Li, Yongming; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping (Frontiers in Immunology, 2022)
SERPINA1, a member of the serine protease inhibitor family, plays a role in viral infection and inflammation by regulating the activities of serine and cysteine proteases. To date, there have been no reports on the immune function of SERPINA1 in fishes. In this study, we first cloned the serpina1 gene of grass carp (Ctenopharyngodon idellus) and found that it could respond rapidly to the infection of Grass carp reovirus (GCRV), and overexpression of serpina1 could enhance the antiviral response of CIK cells. A polyclonal antibody of SERPINA1 was prepared, and the protein interacting with SERPINA1 was screened by CoIP/MS in grass carp liver tissue. It was found that SERPINA1 interacted with coagulation factor 2 (CF2), and SERPINA1 could degrade CF2 in a dose-dependent manner. In addition, the overexpression of cf2 contributes to the infection of GCRV in CIK cells, whereas the co-expression of serpina1 and cf2 in grass carp can reduce the copy number of GCRV in cells. The results showed that grass carp SERPINA1 could inhibit GCRV infection by degrading CF2. This study proposes for the first time that SERPINA1 can inhibit viral infection through the coagulation factor and it provides a new insight into the molecular mechanism of SERPINA1's antiviral function.